2020
DOI: 10.1038/s41598-020-75923-8
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric quantitation of AGEs and enzymatic crosslinks in human cancellous bone

Abstract: Advanced glycation end-products (AGEs) deteriorate bone strength. Among over 40 species identified in vivo, AGEs other than pentosidine were roughly estimated as total fluorescent AGEs (tfAGEs) due to technical difficulties. Using LC-QqTOF-MS, we established a system that enabled the quantitation of five AGEs (CML, CEL, MG-H1, CMA and pentosidine) as well as two mature and three immature enzymatic crosslinks. Human bone samples were collected from 149 patients who underwent total knee arthroplasty. Their clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…This suggests that the porous nature of trabecular bone allows for better access of free-floating sugars to the amino acid residues within the collagen network, resulting in a higher accumulation of AGEs in trabecular bone than in cortical bone ( Karim and Vashishth, 2012 ; Karim et al, 2013 ). Our findings are in line with a previous studies that have reported higher levels of CML in cortical ( Thomas et al, 2018 ) and trabecular bone ( Arakawa et al, 2020 ). Our study provides new information by showing the difference in accumulation of CML in cortical vs trabecular bone and preliminary evidence of its association with bone mechanical properties, which are not reported in earlier studies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This suggests that the porous nature of trabecular bone allows for better access of free-floating sugars to the amino acid residues within the collagen network, resulting in a higher accumulation of AGEs in trabecular bone than in cortical bone ( Karim and Vashishth, 2012 ; Karim et al, 2013 ). Our findings are in line with a previous studies that have reported higher levels of CML in cortical ( Thomas et al, 2018 ) and trabecular bone ( Arakawa et al, 2020 ). Our study provides new information by showing the difference in accumulation of CML in cortical vs trabecular bone and preliminary evidence of its association with bone mechanical properties, which are not reported in earlier studies.…”
Section: Discussionsupporting
confidence: 94%
“…A previous study shows that CML is present in cortical bone in orders of magnitude higher than pentosidine and is correlated with crack propagation toughness, suggesting CML as a valuable representative marker of AGEs in bone ( Thomas et al, 2018 ). Another recent study has reported higher levels of CML compared to pentosidine in human cancellous bone, but no data was reported on the effect of CML on bone mechanical properties ( Arakawa et al, 2020 ). Our goal was to quantify CML in both trabecular and cortical human bone to determine if it differs between the two bone types and to understand if it relates to bone mechanical properties similar to measures of fAGEs.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Direct measures (LC-MS) of CML in human bone, rat and mouse bone have only recently been reported ( Thomas et al, 2018 ; Creecy et al, 2021 ; Arakawa et al, 2020 ; Shirakawa et al, 2016 ). This study highlights quantification of CML in addition to the more traditionally measured enzymatic and non-enzymatic cross-links, which was not possible using traditional high-performance liquid chromatography with fluorescence detection (HPLC-FLD).…”
Section: Discussionmentioning
confidence: 99%
“…While numerous AGEs have been detected in bone collagen, pentosidine (PEN) is the predominantly reported AGE in ( Saito et al, 2006 ; Wang et al, 2002 ; Katayama et al, 1996 ; Kawamura et al, 2019 ; Saito et al, 2010 ; Saito et al, 2006 ; Viguet-Carrin et al, 2006 ; Chavarry et al, 2019 ; Odetti et al, 2005 ; Vaculík et al, 2016 ; Kida et al, 2019 ; Hunt et al, 2018 ; Hunt et al, 2019 ; Heveran et al, 2019 ), yet present in low quantities compared to other AGEs ( Thomas et al, 2018 ). CML is of recent interest ( Thomas et al, 2018 ; Creecy et al, 2021 ; Arakawa et al, 2020 ; Sroga and Vashishth, 2021 ; LLabre et al, 2022 ) but direct quantification of CML between anatomical sites remains a critical knowledge gap. For enzymatic cross-links, LH and LOX control tissue-specific patterning ( Hanson and Eyre, 1996 ; Knott and Bailey, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…are coupled with tandem mass spectrometry (MS/ MS) techniques for identification and determination of an array of glycation adducts. The MS/MS techniques employing atmospheric pressure ionization technology address the need for sensitive detection, positive identification and quantitation of biomolecules and their posttranslational modifications in complex biological matrices [35,[37][38][39][40].…”
Section: Chromatography Techniques Combined With Tandem Mass Spectrom...mentioning
confidence: 99%